Problems of Medical Rehabilitation of Patients with Arterial Hypertension in Clinical Practice (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Problems of medical rehabilitation out in 570 patients admitted to the cardiopulmonary resuscitation and emergency cardiology department of the Bukhara Branch of the Republican Scientific Center for Emergency Medical Aid for 3 years. The frequency of pharmacoinvasive reperfusion and primary percutaneous intervention with complicated and uncomplicated ACS without ST elevation and ST elevation was very low. During treatment, patients were often prescribed convenient medications like low molecular weight heparins (LMWH). According to current clinical guidelines, in patients in the first 12 hours of the disease, the decision to choose primary reperfusion should be made depending on the expected time from the first medical contact (FMC) to a possible primary percutaneous intervention. If this time is less than 120 minutes, the patient must be transported to an angiography laboratory. If this expected time is longer, a TLT should be performed. Treatment of patients with complicated and uncomplicated ACS without ST elevation and ST elevation should be carried out identically and in accordance with current clinical guidelines.